2016
DOI: 10.30554/archmed.16.2.1732.2016
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitación neuropsicológica infantil: de la teoría a la práctica clínica

Abstract: Alrededor del mundo existe una gran cantidad de niños con dificultades cognitivas producto de daño cerebral o trastornos del neurodesarrollo. Estas dificultades traen consigo dificultades de tipo escolar, social, familiar y conductual, entre otras, disminuyendo así la calidad de vida del niño y su familia. Consecuentemente han aumentado en la literatura los artículos que evalúan la utilidad de diferentes programas de rehabilitación neuropsicológica. El objetivo de esta revisión fue (1) determinar cuále… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Search results are indicated in Figure 1. The training of cognitive functions is defined as a dynamic process, in which different strategies of neuropsychological stimulation and rehabilitation converge, characterized by individualizing the procedures, focusing on relevant goals for the subject, considering the emotional and social aspects of the patient and constantly evaluating the profits obtained in the process (Table 1) [18][19][20]. In this sense, cognitive interventions have many names, concepts, objectives and methods, which can be confusing [21].…”
Section: Revision Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Search results are indicated in Figure 1. The training of cognitive functions is defined as a dynamic process, in which different strategies of neuropsychological stimulation and rehabilitation converge, characterized by individualizing the procedures, focusing on relevant goals for the subject, considering the emotional and social aspects of the patient and constantly evaluating the profits obtained in the process (Table 1) [18][19][20]. In this sense, cognitive interventions have many names, concepts, objectives and methods, which can be confusing [21].…”
Section: Revision Methodsmentioning
confidence: 99%
“…Suárez-Yepes et al [20] 2016 Literature review From the theoretical review, it was found that the restorative approach is the predominant in the vast majority of interventions reported in the literature.…”
Section: Key Findings Conclusionmentioning
confidence: 99%